2009
DOI: 10.1074/jbc.m807414200
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Ventricular Myosin Regulatory Light Chain Phosphorylation in Mice Causes Cardiac Dysfunction in Situ and Affects Neighboring Myofilament Protein Phosphorylation

Abstract: There is little direct evidence on the role of myosin regulatory light chain phosphorylation in ejecting hearts. In studies reported here we determined the effects of regulatory light chain (RLC) phosphorylation on in situ cardiac systolic mechanics and in vitro myofibrillar mechanics. We compared data obtained from control nontransgenic mice (NTG) with a transgenic mouse model expressing a cardiac specific nonphosphorylatable RLC (TG-RLC(P؊). We also determined whether the depression in RLC phosphorylation af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
126
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 55 publications
(68 reference statements)
6
126
0
Order By: Relevance
“…Phosphorylation of Ser15 has been recognized to play an important role in cardiac muscle contraction under normal and disease conditions (9). Significantly reduced RLC phosphorylation was reported in patients with heart failure (10, 11) and observed in animal models of cardiac disease (5, [12][13][14]. Attenuation of RLC phosphorylation in cardiac MLCK knockout mice led to ventricular myocyte hypertrophy, with histological evidence of necrosis and fibrosis, and to mild dilated cardiomyopathy (15,16).…”
mentioning
confidence: 99%
“…Phosphorylation of Ser15 has been recognized to play an important role in cardiac muscle contraction under normal and disease conditions (9). Significantly reduced RLC phosphorylation was reported in patients with heart failure (10, 11) and observed in animal models of cardiac disease (5, [12][13][14]. Attenuation of RLC phosphorylation in cardiac MLCK knockout mice led to ventricular myocyte hypertrophy, with histological evidence of necrosis and fibrosis, and to mild dilated cardiomyopathy (15,16).…”
mentioning
confidence: 99%
“…cRLC is partially phosphorylated in vivo under basal conditions (8)(9)(10)(11)(12), and changes in its phosphorylation level are linked to heart disease (8,11,13,14). cRLC mutations associated with hypertrophic cardiomyopathy abolish cRLC phosphorylation in vitro (15), and mice expressing nonphosphorylatable cRLCs show severe cardiac dysfunction (10,16). In the vertebrate heart, cRLCs are phosphorylated almost exclusively by the cardiac isoform of myosin light chain kinase (cMLCK) (17,18), and cMLCK gene ablation leads to severe cardiac hypertrophy (19).…”
mentioning
confidence: 99%
“…Interestingly, following β1-adrenergic stimulation, non-transgenic controls were significantly phosphorylated at RLC Ser-15, which was abrogated in Tg-RLC(P-). The study showed the importance of RLC phosphorylation in maintenance of normal ejection fraction and β 1 -adrenergic responsiveness (Scruggs et al 2009). These reports indicate that maintaining the physiological levels of RLC phosphorylation is critical for the normal function of the heart and suggest that the myocardium containing dephosphorylated myosin, the molecular motor of muscle contraction, has a reduced ability to produce force and maintain cardiac function at physiological levels.…”
Section: Genetic Mutations In Myosin Regulatory Light Chain Lead To Cmentioning
confidence: 96%
“…This claim of a spatial gradient of RLC phosphorylation, however, has been challenged by the Stull group and quantitative measurements have revealed no evidence for its existence in the hearts of WT and transgenic mice overexpressing cMLCK (Huang et al 2008;Kamm and Stull 2011). Significantly depressed Ser-15 RLC phosphorylation was reported in HF patients (van der Velden et al 2003a, b) and was also observed in experimental animal models of cardiac disease (Scruggs et al 2009;Sheikh et al 2012;Yuan et al 2015). Studies in mice showed that reduced RLC phosphorylation resulted in abnormal heart performance, presumably through morphological and/or myofibrillar functional alterations (e.g., change in force, myofilament calcium sensitivity, ATPase activity, cross-bridge kinetics) (Huang et al 2008;Kerrick et al 2009b;Warren et al 2012).…”
Section: Genetic Mutations In Myosin Regulatory Light Chain Lead To Cmentioning
confidence: 99%
See 1 more Smart Citation